A novel cuproptosis-related lncRNAs signature predicts prognostic and immune of bladder urothelial carcinoma - Zhou, Zheng; Zhou, Yusong; Liu, Wei; Dai, Jing (Frontiers in Genetics, 2023)
Bladder Urothelial Carcinoma (BLCA) remains the most common urinary system tumor, and its prognosis is poor. Cuproptosis is a recently discovered novel cell death involved in the development of tumor cells. However, the use of cuproptosis to predict the prognosis and immunity of BLCA remains largely unclear, and this study was designed to verify cuproptosis-related long non-coding RNAs (lncRNAs) to estimate the prognosis and immunity of BLCA. In our study, we first defined the expression of cuproptosis-related genes (CRGs) in BLCA, and 10 CRGs were up- or down-regulated. We then constructed a co-expression network of cuproptosis-related mRNA and lncRNAs using RNA sequence data from The Cancer Genome Atlas Bladder Urothelial Carcinoma (TCGA-BLCA), clinical features and mutation data from BLCA patients to obtain lncRNAs by Pearson analysis. Afterward, univariate and multivariate COX analysis identified 21 lncRNAs as independent prognostic factors and used these lncRNAs to construct a prognostic model. Then, survival analysis, principal component analysis (PCA), immunoassay, and comparison of tumor mutation frequencies were performed to verify the accuracy of the constructed model, and GO and KEGG functional enrichment analysis was used to verify further whether cuproptosis-related lncRNAs were associated with biological pathways. The results showed that the model constructed with cuproptosis-related lncRNAs could effectively evaluate the prognosis of BLCA, and these lncRNAs were involved in numerous biological pathways. Finally, we performed immune infiltration, immune checkpoint and drug sensitivity analyses on four genes (TTN, ARID1A, KDM6A, RB1) that were highly mutated in the high-risk group to evaluate the immune association of risk genes with BLCA. In conclusion, the cuproptosis-related lncRNA markers constructed in this study have evaluation value for prognosis and immunity in BLCA, which can provide a certain reference for the treatment and immunity of BLCA.